The exposure of field-grown maize seedlings to weed volatiles affects their growth and seed quality - Sakurai, Yusuke; Ishizaki, Satomi; Izumi, Shota; Yoshida, Takuma; Shiojiri, Kaori; Takabayashi, Junji (Frontiers in Plant Science, 2023)
Plants exposed to volatiles emitted from artificially damaged conspecific or heterospecific plants exhibit increased resistance to herbivorous insects. Here, we examined whether weed volatiles from artificially damaged plants affect maize growth and reproduction. Seven days after germination, maize seedlings were exposed to volatiles emitted by artificially damaged mugwort (Artemisia indica var. maximowiczii) or tall goldenrod (Solidago altissima) plants either separately, or as a mixture of the two, for seven days. Unexposed seedlings were used as controls. Treated and control seedlings were cultivated in an experimental field without any insecticides applied. Plants exposed to either of the three volatile treatments sustained significantly less damage than controls. Additionally, seedlings exposed to either goldenrod or mixed volatiles produced more leaves and tillers than control plants. Furthermore, a significant increase in the number of ears was observed in plants exposed to the volatile mixture. In all treated plants, ear sugar content was significantly higher than that in the controls. Further, we cultivated seedlings that were either exposed to the volatile mixture or unexposed, under the conventional farming method using pesticides. Similar significant differences were observed for sugar content, number of tillers, leaves, damaged leaves, and ears. Laboratory experiments were conducted to further evaluate the mechanisms involved in the improved performance of volatile-treated plants. A significant reduction in the growth of common armyworm (Mythimna separata) larvae was observed when maize plants were exposed to the volatile mixture. This treatment did not affect the amount of jasmonic acid in the seedlings, whereas salicylic acid content increased upon exposure. The characteristic differences in chemical composition of mugwort and goldenrod volatiles were confirmed and, in turn, the volatile mixture differed significantly from the volatiles of either species.